2009
DOI: 10.3899/jrheum.081088
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Stiffness and Endothelial Dysfunction in Idiopathic and Scleroderma Associated Pulmonary Arterial Hypertension

Abstract: Our study shows a trend towards increased arterial stiffness in scleroderma (nonsignificant), and also peripheral endothelial dysfunction in idiopathic-PAH and in scleroderma-PAH. These findings suggest involvement of different vessels in scleroderma-PAH compared to idiopathic-PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 46 publications
2
52
0
2
Order By: Relevance
“…In our study, the strongest association with subclinical atherosclerosis in SSc was observed with PAH (OR 4). This finding is important because it indicates that microvascular disease in SSc, like PAH with robust data about association with endothelial dysfunction (44,45), may have implications in macrovascular disease and atherosclerosis in SSc.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, the strongest association with subclinical atherosclerosis in SSc was observed with PAH (OR 4). This finding is important because it indicates that microvascular disease in SSc, like PAH with robust data about association with endothelial dysfunction (44,45), may have implications in macrovascular disease and atherosclerosis in SSc.…”
Section: Discussionmentioning
confidence: 76%
“…Timar et al (11) found that augmentation index and PWV were both elevated in 40 patients with SSc and 35 controls. However, several other studies have been unable to demonstrate a significant difference in arterial stiffness between patients with SSc and controls (41,42). Several studies have found an impaired CFR in patients with rheumatic disease who had no evidence of CVD (43,44); very often, the CFR was reduced but still remained above pathologic values, therefore confirming that the prevalence of microvascular in- volvement is high and more common than large-vessel disease (45).…”
Section: Discussionmentioning
confidence: 80%
“…Our findings indicate a relationship between an impaired peripheral endothelial function and the presence and degree of PH in this subset of patients. This relationship has been described in idiopathic pulmonary arterial hypertension, 24 in PH associated with congenital heart disease 25 and in connective tissue diseases, such as scleroderma, 26 but has never before been reported in HFpEF. The presence of PED may be associated with impaired pulmonary endothelial function and could account for the precapillary component of the PH that has been described in these patients.…”
Section: Peripheral Endothelial Dysfunctionmentioning
confidence: 99%